Gastric and intestinal proteases resistance of chicken acidic chitinase nominates chitin-containing organisms for alternative whole edible diets for poultry - Tabata, Eri; Kashimura, Akinori; Wakita, Satoshi; Ohno, Misa; Sakaguchi, Masayoshi; Sugahara, Yasusato; Kino, Yoshihiro; Matoska, Vaclav; Bauer, Peter O; Oyama, Fumitaka (Scientific reports, 2017)
Chitin, a polymer of N-acetyl-D-glucosamine (GlcNAc), functions as a major structural component in crustaceans, insects and fungi and is the second most abundant polysaccharide in the nature. Although these chitin-containing organisms have been suggested as novel animal feed resources, chitin has long been considered as indigestible fibers in the animal body. Recently, we reported that acidic chitinase (Chia) is a protease-resistant major glycosidase in mouse gastrointestinal tract (GIT) and that it digests chitin in the mouse stomach. However, the physiological role of Chia in other animals including poultry remains unknown. Here, we report that Chia can function as a digestive enzyme that breaks down chitin-containing organisms in chicken GIT. Chia mRNA is predominantly expressed in the glandular stomach tissue in normal chicken. We also show that chicken Chia has a robust chitinolytic activity at pH 2.0 and is highly resistant to proteolysis by pepsin and trypsin/chymotrypsin under conditions mimicking GIT. Chia degraded shells of mealworm larvae in the presence of digestive proteases and produced (GlcNAc)2. Thus, functional similarity of chicken Chia with the mouse enzyme suggests that chitin-containing organisms can be used for alternative poultry diets not only as whole edible resources but also as enhancers of their nutritional value.
Keywords: kur domácí; Animals; Chitin; Intestines; Hydrogen-Ion Concentration; Chickens; chitin; Digestion; proteasy; střeva; Peptide Hydrolases; žaludek; Chitinases; Tenebrio; trávení; zvířata; chitinasy; koncentrace vodíkových iontů; Stomach